Publishers tool box updated - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
BookAid s superb list of Information and Training Resources for Publishing and Bookselling is now available online in PDF format, in its 2001- 2002 edition